VD_FINDINFO HC / 2024 / 494 vom 21. Juni 2024 - VD Tribunal cantonal (2024)
FICTION DE LA NOTIFICATION, NOTIFICATION DE LA DÉCISION, CERTIFICAT D'HÉRITIER | 138 al. 1 CPC (CH), 138 al. 3 CPC (CH), 321 al. 2 CPC (CH)